2020
DOI: 10.1007/s11606-020-06042-3
|View full text |Cite
|
Sign up to set email alerts
|

Planning for the Post-COVID Syndrome: How Payers Can Mitigate Long-Term Complications of the Pandemic

Abstract: As the COVID-19 pandemic continues to unfold, payers across the USA have stepped up to alleviate patients' financial burden by waiving cost-sharing for COVID-19 testing and treatment. However, there has been no substantive discussion of potential long-term effects of COVID-19 on patient health or their financial and policy implications. After recovery, patients remain at risk for lung disease, heart disease, frailty, and mental health disorders. There may also be long-term sequelae of adverse events that devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 24 publications
(27 reference statements)
2
64
0
8
Order By: Relevance
“…Although retrieved from a basic questionnaire, the results obtained from this study are statistically significant. Our findings are consistent with data obtained from similar studies in other countries [ 43 , 44 ]. In this study, no significant relationship between blood group and post-COVID-19 short-term outcome was found.…”
Section: Discussionsupporting
confidence: 94%
“…Although retrieved from a basic questionnaire, the results obtained from this study are statistically significant. Our findings are consistent with data obtained from similar studies in other countries [ 43 , 44 ]. In this study, no significant relationship between blood group and post-COVID-19 short-term outcome was found.…”
Section: Discussionsupporting
confidence: 94%
“…Upośledzenie zdrowia psychicznego, w tym objawy depresji, lęku i zaburzeń stresu pourazowy (PTSD), są powszechnie zgłaszane przez osoby, które przeżyły krytyczną chorobę (odpowiednio u 30%, 32% i 20%), utrzymujących się przez ponad 1 rok. Można się spodziewać, że przeżycie COVID-19 może spowodować problemy związane z PICS [37] Autorzy zwracają uwagę na ryzyko występowania u osób ocalałych takich chorób, jak: choroby płuc, choroby serca, osłabienie i zaburzenia zdrowia psychicznego. Postulują wprowadzenie kompleksowego planu zapobieganie i leczenie powikłań po COVID-19 [38] Artykuł podnosi temat wpływu COVID-19 na obniżenie sprawności mózgu, która stać może za występowaniem uporczywych objawów zaburzeń psychicznych u osób ocalonych, w tym zespołu psychicznego zmęczenia.…”
Section: Wyniki Przeglądu Literaturyunclassified
“…It has been reported that long-term health complications and sequelae are common with COVID-19 infection among those with medical and psychological problems. [45] The economic burden related to COVID complications and disability are anticipated to be high. Addressing the known infrastructure and socio-cultural issues is a significant way to address the short-and long-term consequences of COVID-19.…”
Section: Recommendationsmentioning
confidence: 99%